Pain control of thoracoscopic major pulmonary resection: is pre-emptive local bupivacaine injection able to replace the intravenous patient controlled analgesia? - Yang, Hee Chul; Lee, Ja-young; Ahn, Soyeon; Cho, Sukki; Kim, Kwhanmien; Jheon, Sanghoon; Kim, Jun Sung (Journal of Thoracic Disease, 2015)
Background: The aim of this open-label, non-inferiority trial was to evaluate whether pre-emptive local bupivacaine injection (PLBI) can replace intravenous patient controlled analgesia (IV PCA) in video-assisted thoracic surgery (VATS) major pulmonary resection. Methods: A total of 86 patients scheduled for VATS segmentectomy/lobectomy were randomly assigned into two groups. The PLBI group (n=42) received 0.5% bupivacaine wound infiltration before skin incision, and the IV PCA group (n=44) received a continuous infusion of fentanyl with a basal rate of 10 μg/mL/hr. Visual analogue scale (VAS; range, 0-10) was measured as the primary endpoint. The secondary endpoint was an additional use of analgesics and drug induced side effects. Results: Both groups showed no difference in terms of age, sex, disease entity, operation time, chest tube indwelling time, and hospital stay. Serial pain scores between the PLBI and IV PCA groups demonstrated no statistical differences (non-inferiority margin; ΔVAS =1.0) (Recovery room: 8.3±2.1 vs. 8.5±1.7; Day 0: 5.1±1.6 vs. 5.2±1.4; Day 1: 3.5±1.6 vs. 3.3±1.2; Day 2: 2.7±1.3 vs. 2.5±1.2; Day 3: 2.3±1.3 vs. 2.1±1.5; 1 week after discharge: 3.0±1.7 vs. 2.8±1.5; 1 month: 1.9±1.2 vs. 2.3±1.4 and 2 months: 1.5±1.2 vs. 1.3±1.2; 95% confidential interval (CI) of ΔVAS 0.05). The mean one-additional usage of IV analgesics was needed in the PLBI group (3.3±2.1 vs. 2.3±1.3; P=0.03). The occurrence of nausea/vomiting was higher in the IV PCA group (12.5% vs. 38.9%; P=0.026) and 41.7% of IV PCA patients experienced drug side effects that required IV PCA removal within postoperative day (POD) 1. Conclusions: PLBI is a simple, safe, effective, and economical method, which is not inferior to IV PCA in VATS major pulmonary resection.